Upaya Mengefektifkan Proses Menyusui Pada Ibu Nifas - Amaliya, Kamila; , Winarsih Nur Ambarwati, S.Kep., Ns., ETN., M.Kep; , Sulastri, S.Kp., M.Kes (2017)
Background: Breastfeeding is giving milk to the baby in breast milk from the mother's breast. Babies use sucking reflex to obtain and ingest milk. A baby can be nursed by his own mother or another woman (Yohana, 2011). WHO and UNICEF recommend to the mother, if possible exclusive breastfeeding until 6 months of applying 1. Early Initiation of Breastfeeding for approximately 1 hour immediately after birth. 2. Exclusive breastfeeding is given to infants only breast milk without any additional food or drink. 3. ASI supplied on demand or according to the baby's needs, every day for 24 hours. Purpose: The purpose of nursing care is to streamline the process of breastfeeding in mothers during childbirth, so that the milk comes out smoothly and the patients get satisfaction when breastfeeding and the baby getting enough nutrients. Methods: The method used descriptive which describe or depict characters postpartum mothers whose supply has not come out smoothly and with the approach of case study that the nature of the scientific method of collecting data, analyzing data, and draw conclusions from existing data. Assessment beginning on February 9, 2017. The process of data collection by direct interview to the patient and family, doing a physical examination, observe and make a documentary study using a journal or book related. In this case the authors make the process of nursing care that focuses on efforts to streamline the process of breastfeeding on postpartum mother in patients Ny. E who has just given birth to her second child and is in postnatal days to two. In this case the authors implemented by using health education to patients to increase milk production. Results: The results of the above objectives can be concluded that after three visits in one week the issue is resolved in part, milk production increased slightly.